2017
DOI: 10.1371/journal.pone.0184737
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of histologic subtypes in locally advanced esophageal carcinoma treated with pre-operative chemoradiotherapy: Experience of a monographic oncologic centre

Abstract: BackgroundLocally advanced esophageal carcinoma (LAEC) represents less than 30% of all diagnosed esophageal carcinoma worldwide. The standard of care for resectable tumours consists of preoperative chemoradiotherapy (CRT) followed by surgery. Despite the curative intent, the prognosis is still poor mainly due to relapse. A multidisciplinary approach is required in order to optimize the therapeutic strategy and follow-up. Differences in outcomes between the two main histological subtypes, adenocarcinoma (ADC) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…A recent study of Saigi et al declared that patterns of disease recurrence differentiate regarding histological tumor subtype. According to this study, distant metastasis was more abundant in adenocarcinoma, whereas local disease recurrence was related to SCC (62% versus 50%, p=0.027) [38].…”
Section: Discussionmentioning
confidence: 47%
“…A recent study of Saigi et al declared that patterns of disease recurrence differentiate regarding histological tumor subtype. According to this study, distant metastasis was more abundant in adenocarcinoma, whereas local disease recurrence was related to SCC (62% versus 50%, p=0.027) [38].…”
Section: Discussionmentioning
confidence: 47%
“…[38][39][40] Conversely, other studies have suggested that the pattern of recurrence is heavily influenced and have shown that patients with ESCC treated with neoadjuvant chemoradiotherapy followed by surgery have a higher incidence of locoregional recurrence. 2,7,[41][42][43] Ultimately, our analysis may be limited due to the variation in the neoadjuvant treatment regimens given, our decision to include patients who received no neoadjuvant treatment, and the small sample size of patients with isolated regional recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Such facts could be the result of a probable predominance in the carcinoma histological subtype of squamous cells, which have a relationship that is inversely proportional to the human development index (21) . Besides that, this type of cancer has demonstrated better survival rates and a lower rate of relapse in comparison to adenocarcinomas (14) . Inequality in the country persists, even though enhancements were verified in the last years (27) .…”
Section: Discussionmentioning
confidence: 99%
“…However, more than 30% of patients develop metastasis, lowering the survival rate in five years to 4.5% (1) . Differences in the outcome of treatment, in terms of survivability and recurrence, can be found according histological type, but it also depends on the state of the disease and the treatment done (13,14) .…”
Section: Introductionmentioning
confidence: 99%